Communicating Physical Activity with Adolescents: What works? A scoping review protocol - Grady Caera; Ng Kwok; Murtagh Elaine; Woods Catherine (Health Research Board, 2025)
Background: Worldwide, adolescents are not meeting the minimum recommended physical activity (PA) guidelines to achieve health benefits. Awareness of the guidelines among adolescents is low, only 3.6% can report them correctly. The school is an ideal PA promotion setting, no other institute has the same reach or influence on the adolescent population. There is a need for an effective communication strategy for PA messages for adolescents. The purpose of this review is to explore how, when, who, where and what i.e. the content, context and mode of delivery of PA messages to communicate with adolescents to improve their awareness and understanding of PA that will potentially lead to an increase in PA levels. Methods: A scoping review was selected as the most appropriate methodology due to the broad nature of the research question. The PCC mnemonic (Population, concept, context), recommended by the Joanna Briggs Institute, was used to develop the search strategy and research question. This review will follow the scoping review framework developed by Arksey and O'Malley (2005) which was later updated by Levac et al (2010) to ensure the methods are systematic. It will also follow the PRISMA extension for scoping reviews checklist. Sources include databases (CINAHL, Education Source, Scopus, PubMED), grey literature from the World Health Organisation, Global Index Medicus and the reference lists of extracted articles will be checked from the year 1995 onwards. Results: A PRISMA flow diagram will demonstrate the final articles included and results will be presented and summarised as recurring themes. The results will be discussed in relation to existing literature and future implications for research, policy and practice. Conclusion: This will be the first review to explore the PA messaging context among adolescents and the findings will help inform a strategy for communicating PA to adolescents.